Missense variant analysis in the TRPV1 ARD reveals the unexpected functional significance of a methionine - Grace C. Wulffraat; Sanjana Mamathasateesh; Rose Hudson; Benjamin He; Andrés Jara-Oseguera; Eric N. Senning (PLoS ONE, 2025)
The Transient Receptor Potential Vanilloid sub-type 1 (TRPV1) is an ion channel that is activated by heat, extracellular protons, oxidation, and it is implicated in various aspects of inflammatory pain. In this study, we uncover that residue M308 in the TRPV1 ankyrin repeat domain (ARD) stands out from most other buried ARD residues because of the greater number of human missense variants at this position while maintaining a high degree of conservation across species and TRPV channel subtypes. We use mutagenesis and electrophysiology to examine this apparent discrepancy and show that substitutions at position M308 that preserve or reduce side-chain volume have no effect on channel function, whereas substitutions with larger or more polar residues increase channel activity in response to capsaicin or temperature. Substitution of M308 with a histidine bestows channels with pH-dependence that is different from wild type, consistent with the side-chain at position 308 exerting an influence on channel gating. We speculate that M308 is highly conserved because its side-chain could serve as a target for oxidation-dependent modification. On the other hand, we show that a previously described splice variant of TRPV1 that relies on M308 as a start codon diminishes surface expression of co-transfected full-length TRPV1 in HEK293 cells. Together, our findings reveal a functionally important conserved site within the ARD of TRPV1 that could have roles in oxidation-dependent channel regulation as well as tuning the number of active channels in the membrane by enabling expression of a shorter dominant-negative splice variant.